The Role of the Gut Microbiota in the Pathogenesis of Parkinson's Disease - Yang, Dongming; Zhao, Deming; Ali Shah, Syed Zahid; Wu, Wei; Lai, Mengyu; Zhang, Xixi; Li, Jie; Guan, Zhiling; Zhao, Huafen; Li, Wen; Gao, Hongli; Zhou, Xiangmei; et al. (Frontiers in Neurology, 2019)
It is well recognized that the gut microbiota (GM) is crucial for gut function, metabolism, and energy cycles. The GM also has effects on neurological outcomes via many mechanisms, such as metabolite production and the gut-brain axis. Emerging evidence has gradually indicated that GM dysbiosis plays a role in several neurological diseases, such as Parkinson’s disease (PD), Alzheimer’s disease, depression, and multiple sclerosis. Several studies have observed that PD patients generally suffer from gastrointestinal disorders and GM dysbiosis prior to displaying motor symptoms, but the specific link between the GM and PD is not clearly understood. In this review, we aim to summarize what is known regarding the correlation between the GM and PD pathology, including direct and indirect evidence.